A revision of the New World sharpshooter genus Xyphon Hamilton (Hemiptera: Cicadellidae: Cicadellinae) - Catanach, Therese A.; Dietrich, Chris H.; Woolley, James B. (Zootaxa, 2013)
A phylogenetic analysis of Xyphon was completed using 45 adult morphological characters and 1,076 base pairs of the mtDNA gene NADH dehydrogenase 1. Multiple specimens, representative of the range of morphological variation found in each previously described species, were scored for the morphological data matrix to test the monophyly of each species. These tests supported the following synonymies: Xyphon gillettei (Ball, 1901) to include X. balli (Knull, 1940) syn. nov.; and X. reticulatum (Signoret, 1854) to include X. diductum (Fowler, 1900) syn. nov., X. dyeri (Gibson, 1919) syn. nov., and X. sagittiferum (Uhler, 1895) syn. nov. Parsimony and Bayesian techniques were used to infer relationships among species, resulting in almost identical tree topologies. In all analyses Xyphon was monophyletic and Draeculacephala was its sister genus although clade support for Xyphon was generally low. The analyses suggest that a clade comprising X. flaviceps (Riley) and X. fulgidum (Nottingham) is sister to the remainder of the genus, and a clade comprising X. gillettei and X. spadice sp. nov. was sister to a clade containing X. triguttatum (Nottingham), X. nudum (Nottingham), and X. reticulatum. The six currently recognized species, including X. spadice sp. nov., are described and illustrated and a key to adult Xyphon is provided.